2005
DOI: 10.1111/j.1095-8649.2005.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen on the growth of Oncorhynchus mykiss embryos with and without a chorion

Abstract: Growth was measured in dechorionated and chorionated embryos of rainbow trout Oncorhynchus mykiss exposed to three oxygen treatments: hypoxia, normoxia and hyperoxia (nominally 5, 10 and 15 mg l À1 ). Dechorionated embryos grew faster than chorionated ones in all three oxygen treatments. Similar patterns, however, were found in both dechorionated and chorionated groups; embryos exposed to hypoxia grew less than normoxic and hyperoxic exposed embryos. Moreover, there was no significant interaction between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…The outside of the pore canals are plugged making the chorion a semipermeable membrane, which allows only small molecules (including oxygen) to diffuse through (Groot and Alderdice, 1985;Eddy et al, 1990). We concluded that the chorion was not a barrier to oxygen diffusion based on body mass data of trout embryos with and without an intact chorion (Ciuhandu et al, 2005). We found, however, that intact embryos in normoxia attained the same body mass as dechorionated embryos in hypoxia (50% saturation), suggesting that the chorion may restrict oxygen uptake.…”
Section: Introductionmentioning
confidence: 93%
“…The outside of the pore canals are plugged making the chorion a semipermeable membrane, which allows only small molecules (including oxygen) to diffuse through (Groot and Alderdice, 1985;Eddy et al, 1990). We concluded that the chorion was not a barrier to oxygen diffusion based on body mass data of trout embryos with and without an intact chorion (Ciuhandu et al, 2005). We found, however, that intact embryos in normoxia attained the same body mass as dechorionated embryos in hypoxia (50% saturation), suggesting that the chorion may restrict oxygen uptake.…”
Section: Introductionmentioning
confidence: 93%
“…Dissolved O 2 was monitored daily in the normoxic (98.7±0.4%) and hypoxic (29.7±0.5%) treatment tanks throughout the experiment (Hach LDO101 electrode connected to Hach HQ30d meter, Hach Company, Mississauga, ON, Canada). Because hypoxia exposure delays salmonid development (Shumway et al, 1964;Hamor and Garside, 1976;Ciuhandu et al, 2005;Miller et al, 2008), embryo sampling was stage-matched for the two treatment groups. Embryos were sampled at Vernier Stages 27 (prehatch; circulatory system is formed and functioning), 30 (hatch), 32 and 33 (in preliminary experiments a large increase in P 50 was observed between these stages), and 35 (near-complete yolk absorption; Fig.…”
Section: Experimental Protocol Treatment Conditionsmentioning
confidence: 99%
“…In addition, the encapsulated, non-motile embryos may remain under these conditions for up to 5 months prior to emergence (Youngson et al, 2004). Previous work has demonstrated that embryonic development of teleost fish is extremely sensitive to environmental conditions (Ørnsrud et al, 2004) and that chronic hypoxia exposure delays development in fish (Shumway et al, 1964;Hamor and Garside, 1976;Ciuhandu et al, 2005;Spicer and Burggren, 2003;Bagatto, 2005;Miller et al, 2008). The reduction in developmental rate represents an adaptive response to reduce O 2 demand (Miller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%